"The Internal Police Officer Has Not Retired but Has Slowed Down": Israeli Women Reframe Their Aging Experiences in the Second Half of Life. (March 2022) - Ayalon, Liat; Lir, Shlomit Aharoni
Compared with gains, losses have received a substantial amount of research and public attention. The present study aims to shed light on the positive gains associated with older age from the perspective of older women. Five focus groups with 19 Israeli women over the age of 54 were conducted. Trailers of three different films were used to stimulate discussion about old age and aging and allow for reflections on societal norms in light of personal experiences. Focus group interviews were analyzed thematically. Respondents identified four contexts, characterized by reframing their experiences against societal norms. These included gender stereotypes, physical appearance, interpersonal relations, and employment. This study represents an opening to a different discourse around old age, which is characterized by gains and possibilities brought about by changes in reframing one's experiences, while distancing oneself and exerting free will vis à vis social norms.